PENILAIAN TANAMAN NILAM DALAM MEREMEDIASI LOGAM CADMIUM PENGARUHNYA PADA PERTUMBUHAN DAN KANDUNGAN MINYAK ATSIRI - Yustina Sri Sulastri; Delima Panjaitan (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Heavy metal pollution in urban soil is an increasingly urgent problem today. High concentrations of heavy metals in soil can cause long-term risks to ecosystems and humans. It is necessary to find a solution to reduce heavy metal pollution, especially through phytoremediation using patchouli plants. Research on patchouli plants was carried out using a non-factorial randomized block design; consists of 1 factor, namely the concentration of the heavy metal Cd which consists of five levels: K0= 0 ppm, K= 85 ppm, K2= 170 ppm, K3= 255 ppm, K4= 340 ppm. Each treatment was made in 3 replications where each experimental unit consisted of 3 plants. Data on essential oil content and uptake of the heavy metal Cd from the results of this study were analyzed using IBM SPSS Statistics 20, then the treatment that showed a real influence on the observed variables was continued with the Duncan's Multiple Range Test (DMRT) at a confidence level of 5%. The parameters observed were root length (cm), root volume (cm3), root wet and dry weight (g), shoot wet and dry weight (g), essential oil content (ml/g), cadmium uptake in the roots and shoots. (ppm). The research results show that patchouli plants are classified as plants that are resistant to heavy metal stress, this can be indicated by their ability to grow and develop well at concentrations ranging from 0 ppm to 255 ppm. Based on the absorbed Cd content, patchouli plants are classified as phyto-extraction plants because they are able to accumulate greater Cd metal in their shoots compared to the Cd content in their roots. Likewise, the production of essential oils produced is not influenced by the concentration of Cd metal.